Effectiveness Of Modified Planks on Trunk Stability in Post-Stroke Hemiplegic Patients: A Randomized Control Trial. - T. Gaikwad, Srushti; Yadav, Trupti (Journal of Neonatal Surgery, 2025)
Introduction- Stroke patients who are treated in their early stages of recovery have better chances of achieving maximum optimal functioning of their body. It is also important to continue the protocol in progression according to patient’s stage of recovery. A plank is a type of isometric core exercise which is not regularly used in Out-Patient department (OPD) protocol of stroke patient’s rehabilitation. But planks have effect in strengthening core muscles, which will ultimately improve trunk control helping stroke patients to achieve their goals. These planks can be modified according to ability of stroke patient for their trunk control. Aim- To discover effect of modified Planks exercises on trunk stability in post-stroke hemiplegic patients. Methods & materials- 20 consenting stroke patients with Brunnstrom recovery stage 4 and above were included according to inclusion criteria. They were evaluated on outcome measure -Trunk Impairment Scale (TIS) and Timed Up and Go test (TUG). 1 week of exercise interventional program was followed by them. Results- About 20% of the participants were in Brunnstrom recovery stage 6. The average TIS score post the intervention was 19 and 15 in experimental and control group respectively. P value (0.0002 & <0.0001) of TIS & TUG scores is statistically significant in experimental group. Conclusion- Modified planks seemed to be significantly productive in enhancing trunk stability in hemiplegic patients with Brunnstrom recovery stage 4 and above. In comparison with control group, experimental group has significant improvement in trunk stability, according to TIS and TUG scores.